Voluntary Associations and the Rule of Law - Oza, Manish (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2026)
Voluntary associations (groups such as unions, political parties, and clubs) are subject to natural justice requirements in private law. When they make decisions that affect their members’ rights, they have to act in a procedurally fair way. This article is about why this is. Two well-understood sources of normative constraint fail to make sense of these requirements. First, one might argue that the requirements are an instance of the legitimacy conditions that apply to public authorities. While this view explains natural justice requirements on voluntary associations, it also generates too many other requirements. Second, one might argue, drawing from Kantian private law theory, that any limits on voluntary associations must be derived from the formal limits on property and contract rights. While this view leaves room for natural justice requirements, it does not explain why they should apply. I argue that voluntary associations organize human conduct using what Lon Fuller called “the legal principle”: authority grounded in reciprocity. To the extent that groups organize their member’s conduct in this way, they have to conform to the rule of law. Natural justice requirements are an aspect of the rule of law.